ANALYSIS OF THE STATE OF THE DEVELOPMENT OF AIRBORNE RADARS OF DOMESTIC AND FOREIGN PRODUCTION - E. E. Nechayev; K. S. Deryabin (Научный вестник МГТУ ГА)
This article gives a brief description of the of modern and advanced aircraft systems and multi-functional on-board radar stations as part of their avionics, the characteristics of airborne radars and description of antenna arrays op-erationally available in Russia and abroad. It`s also shows possible ways of development of on-board radars in the near future.